(untitled) (Journal of Geography and Environmental Management, 2024)
Studying the floristic composition and dynamics of vegetation in pasture landscapes is of great importance. Pasture landscapes serve as a resource for livestock development, where processes of overgrazing and undergrazing, depletion of their flora, and reduced productivity of phytocenoses are currently observed. Studying the plant communities of pasture landscapes is relevant because assessing the condition of pasture landscapes and developing land management and ameliorative measures for them contribute to increasing their productivity and preserving landscapes as a whole. The natural fodder lands of the western part of the territory of the Zhanibek and Kaztal districts of the West Kazakhstan region served as the object of the study. The current state of natural pastures and hayfields has been studied, and a landscape-typological classification of pasture landscapes of the research objects has been compiled. Materials from geobotanical surveys have been analyzed. A modern landscape-typological classification of pasture landscapes has been developed, which combines 2 classes of pastures (semi-desert-steppe pastures on light-chestnut and saline soils and steppe pastures on chestnut soils), 4 subclasses of pastures (plain-flat, slightly inclined plane, slightly inclined plane with slightly dissected gully networks, gully-flat), and 14 groups of pasture landscapes, each with a brief description. Within the research objects, 14 groups of pasture landscapes have been identified with descriptions of characteristic plant communities and predominant soils. Natural pasture landscapes have been studied using field and satellite methods. It is recommended to use them as summer-autumn-spring pastures for coarse-haired and fine-haired sheep breeds, large horned cattle, horses, and saigas, and as winter pastures for horses and saigas.